Javanese Language Maintenance Through Javanese Traditional and Modern (Folk) Songs - Wiwiek Sundari (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2020)
Javanese Language is learnt and studied by many people throughout the world as it has a complex system of language covering the letters (Javanese Language Orthography), the politeness level, and also the history and the culture behind the language. However, there is a concern on Javanese Language shift by its young speakers because they tend to use Indonesian Language as Indonesia’s Official Language, English as the world’s international language, or another popular language in the world like Korean with its K-Pop phenomenon. Javanese Language maintenance is then needed to keep these young generation as the language users who will pass it to the next generation. One of the ways to do it is embracing their world so that the language is considered good and beneficial for them as the young generation. Since music and song is very close to the young generation as they are very up to date with the latest trend of it, the language maintenance can be done through exposing Javanese kinds of music and songs. Recently, a kind of Javanese music called Campursari along with its songs are gaining popularity with the fame of The Godfather of The Brokenheart, Didi Kempot, who creates thousands of Campursari songs full of love stories in the lyric, particularly the brokenheart storied. Out of nowhere, the young generation, who are Javanese, who are Javanese but do not understand Javanese Language or even who are not Javanese and not understand Javanese Language are joining the crowd and becoming his fans that previously filled with the old generation. This research shows how Junior Highschool Students maintain the Javanese Language usage by liking the music, singing the songs and understanding the Javanese Language in the lyric. This research also observes whether they still know or able to sing traditional Javanese songs they exposed from their family, environment (neighbourhood) or Javanese Language class at school that shows their Javanese Language maintenance. Keywords: language maintenance, Javanese Language, students, Junior Highschool, Campursari, Javanese music and song